Analysis of SAW and WP Methods in Selecting the Best Employee - Hary Saputra; Reza Randika; Selipana; Emi Sita Eriana (MultiTech Publisher, 2024)
In today's digital era, selecting the best employees in this case effective Customer Service is one of the key factors in increasing customer satisfaction and brand loyalty. This article discusses the analysis of the Simple Additive Weighting (SAW) and Weighted Produ ct (WP) methods in the context of selecting new employees. The SAW method is a decision-making technique that prioritizes the sum of the weights of predetermined criteria, while WP gives weight to each alternative based on the multiplication of relevant criteria . In this research, we conducted a case study on a company engaged in Customer Service. We identified several important criteria for customer service assessment, such as response speed, communication quality, and problem-solving rate. The results of the analysis show that the SAW method is simpler and easier for managers to understand in the decision-making process, while WP provides more comprehensive results by considering interactions between criteria. Although both methods show consistent results in the selection of the best Customer Service, the use of the WP method provides an advantage in situations where the interdependence between criteria is very significant. The conclusion of this article emphasizes the importance of choosing the right analysis method in making decisions regarding the best customer service. By understanding the advantages and disadvantages of each method, companies can be more effective in improving service quality and meeting customer expectations.